Accuracy, reliability, and efficiency of intraoral scanners for full-arch impressions: a systematic review of the clinical evidence - Goracci, Cecilia; Franchi, Lorenzo; Vichi, Alessandro; Ferrari, Marco (European journal of orthodontics, 2016)
The interest on intraoral scanners for digital impressions has been growing and new devices are continuously introduced on the market. It is timely to verify whether the several scanners proposed for full-arch digital impressions have been tested under clinical conditions for validity, repeatability, reproducibility, as well as for time efficiency, and patient acceptance. An electronic search of the literature was conducted through PubMed, Scopus, Cochrane Library, Web of Science, and Embase, entering the query terms 'digital impression', 'intraoral digital impression', 'intraoral scanning', 'intraoral scanner', 'intraoral digital scanner', combined by the Boolean operator 'OR'. No language or time limitation was applied. Only studies where digital full-arch impressions had been recorded intraorally were considered. In only eight studies full-arch scans had been performed intraorally. Only four studies reported data on validity, repeatability, reproducibility of digital measurements and their samples were limited to subjects in complete permanent dentition. Only two intraoral scanners, Lava COS and iTero, were tested. Scanning times were measured in six studies and varied largely. Patients' acceptance of intraoral scanning was evaluated in four studies, but it was not specifically assessed for children. The scientific evidence so far collected on intraoral scanning is neither exhaustive, nor up-to-date. Data from full-arch scans performed in children should be collected. For a meaningful assessment of time efficiency, agreement should be reached on the procedural steps to be included in the computation of scanning time.